Risk factors of single episode major depressive disorder among patients in four tertiary government hospitals in Selangor and the Federal Territory, Malaysia - Abul Razak, Nurul Asyikin (2019)
Major Depressive Disorder (MDD) is one of the most common and serious psychiatric disorders worldwide. It is associated with impairment in role functioning and quality of life. This psychiatric problem is often under detected and under treated despite its common occurrence in general population. MDD has multifactorial etiological causes which include genetic, neurobiological, psychological and social factors. Personality traits and stressful life events are significant psychosocial factors in MDD. In Malaysia, there was a lack in study of this established psychosocial factors associated with first onset of MDD. Various studies focused on the prevalence of depressive symptoms and it associated factors in different settings and different target groups. There is no study that investigate the association of personality traits and stressful life events associated with single episode of MDD. The study aimed to determine personality traits & stressful life events as psychosocial risk factors among patients with single episode MDD attending government hospitals in Malaysia. This was a matched case-control study design. A total of 297 cases and 297 controls matched by age, sex and ethnicity were recruited in four government hospitals in Malaysia. The case subjects were recruited among patients with single episode of MDD attending Psychiatry Outpatient Clinics. Whereas, the controls were individuals who accompanied the patients attending Orthopedic Clinic, Surgical Clinic and ENT Clinic in the same local hospital with cases. The convenience sampling method was used. All the new patients with the diagnosis of single episode of MDD attending four government hospitals as registered in outpatient clinic were screened for inclusion and exclusion criteria. Prior to study entry, all the eligible subjects who fulfilled the inclusion and exclusion criteria were given informed consent form and study information sheets. Face to face interviews were conducted utilizing the Mini International Neuropsychiatric Interview (MINI) to confirm the diagnosis of MDD and Montreal Cognitive Assessment Scale (MoCA) questionnaires to exclude any global cognitive impairment. Self-administered survey questionnaires were utilized for the data collection which were socio-demographic profiles, clinical characteristics, the list of Threatening Experiences and Temperament & Personality Questionnaire. IBM SPSS Statistics Version 25 and Stata Software Version 13 were used to perform the statistical analyses. Descriptive statistics, Chi-square analysis, McNemar’s test and conditional logistic regression analysis were used to analyze the collected data based on the study objectives. A response rate of 98.02% was achieved when all the subjects completed the data. The Chi-square analysis showed that there was statistically significant difference in marital status, job status, family income educational level and family history of mental illness between the MDD subjects and healthy controls. Meanwhile, the result from McNemar’s test discovered that there was statistically significant association between life events and MDD. It also indicated that the association between all personality traits except for perfectionism and MDD were statistically significant. Conditional logistic regression analysis revealed that six variables were found to be predictors of MDD. The strongest predictors for MDD in descending order were family history of mental illness, stressful life event, interpersonal sensitivity, employment status, self-criticism and effectiveness. In conclusion, the findings from this study examined the links of stressful life events and personality traits on the risk of onset of MDD. The focus should be given to the strategies in giving the treatment and early screening for risk factors in clinical setting. The preventative programs should be aimed to reduce the risk of becoming depressed by enhancing coping and self-management skills in high risk group. Further prospective cohort studies should be carried out to assess the causal relationship of single episode of MDD and its risk factors among population in Malaysia.